2016
DOI: 10.1080/13803395.2016.1252724
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute beta-adrenergic antagonism on verbal problem solving in autism spectrum disorder and exploration of treatment response markers

Abstract: Autism spectrum disorder (ASD) is characterized by impairments in social communication as well as restricted, repetitive behaviors. Evidence suggests that some individuals with ASD have cognitive impairments related to weak central coherence and hyperrestricted processing. Reducing noradrenergic activity may improve aspects of network processing and thus improve cognitive abilities, such as verbal problem solving, in individuals with ASD. The present pilot study explores the effects of acute administration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 55 publications
0
30
1
Order By: Relevance
“…Pharmacological system Effects NORADRENERGIC Beta-adrenergic effects on convergent tasks under stress [8] and in pathological states [26,27], and with challenging tasks [11] Beta-adrenergic effects on divergent tasks in pathological states [28] COMT gene polymorphisms effect on insight-based problem solving [69]…”
Section: Summary Of Effects Of Pharmacological Systems Associated Witmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological system Effects NORADRENERGIC Beta-adrenergic effects on convergent tasks under stress [8] and in pathological states [26,27], and with challenging tasks [11] Beta-adrenergic effects on divergent tasks in pathological states [28] COMT gene polymorphisms effect on insight-based problem solving [69]…”
Section: Summary Of Effects Of Pharmacological Systems Associated Witmentioning
confidence: 99%
“…Also, consistent with this, performance on creativity tasks has been found to be better in the setting of 'leaky sensory gating' as indicated by the P50 ERP [24••], which is of particular interest given recent evidence from neuroimaging studies that demonstrate increased gain in the precision of cortical representations associated with both markers of baseline catecholamine levels and administration of the norepinephrine transporter blocker atomoxetine [25]. Propranolol can also benefit performance on verbal problem solving for the easiest problems in situations where there is upregulated activity of the noradrenergic system due to cocaine withdrawal [26] and psychosocial stress [8••], or where there is a physiological or anatomical alteration of the language network resulting in loss of flexibility due to conditions such as autism spectrum disorder (ASD) ( for both convergent task effects [27] and divergent task effects [28]) and benefits are also seen for naming in Broca's aphasia due to stroke [29]. More recently, these benefits in ASD with propranolol have also been observed in the social domain [30] ( Table 2).…”
mentioning
confidence: 99%
“…Three controlled studies found that single-dose propranolol improves language. In a small ( n = 20) DBPC crossover study of adults and adolescents with ASD, propranolol treatment improved the speed of solving verbal anagram problems with the improvement related to autonomic activity and anxiety [ 153 ]. Still, in another small ( n = 14 individuals with ASD, 14 control individuals) DPBC crossover study on adults and adolescents with HFASD, propranolol improved category fluency, but not letter fluency [ 154 ].…”
Section: Drug Treatments For Improving Social Interaction In Autism Smentioning
confidence: 99%
“…Lastly, there was no significant change in self-reported anxiety scores as measured by the Beck Anxiety Inventory and the Spence Children's Anxiety Scale after the administration of propranolol (Zamzow et al, 2016), which was also replicated by Zamzow et al (2017) at a later date. Lastly, Zamzow et al (2017) conducted further analyses into autonomic activity. Prior to each testing session baseline electrocardiography (ECG), required to calculate heart rate variability (HRV), and skin conductance were measured.…”
Section: Cognitive Performancementioning
confidence: 80%